2019
DOI: 10.1002/open.201900316
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Tandem Assay for Pyridoxal‐5′‐phosphate by the Reporter Pair of Guanidinocalix[5]Arene and Fluorescein

Abstract: This is an open access article under the terms of the Creative Commons Attribution Non-Commercial NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Scheme 1. Schematic illustration of STA constructed by GC5A-6C · Fl reporter pair to detect PLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The enzymatic activity could be monitored by the detectable fluorescence response [19] . STA represents advantages of being fast, affordable, and remarkably simple, which has demonstrated wide applications in enzymatic activity monitoring, inhibitor and activator screening, [20] sensor array, [21] and membrane transport [22] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymatic activity could be monitored by the detectable fluorescence response [19] . STA represents advantages of being fast, affordable, and remarkably simple, which has demonstrated wide applications in enzymatic activity monitoring, inhibitor and activator screening, [20] sensor array, [21] and membrane transport [22] …”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic activity could be monitored by the detectable fluorescence response. [19] STA represents advantages of being fast, affordable, and remarkably simple, which has demonstrated wide applications in enzymatic activity monitoring, inhibitor and activator screening, [20] sensor array, [21] and membrane transport. [22] Supramolecular hosts are a family of well-designed artificial receptors with a discrete cavity that provides efficient hostguest interactions to certain biological substances.…”
Section: Introductionmentioning
confidence: 99%
“…30 The recent study revealed that cofactor PLP showed the higher inclusion complexing ability with β-CD than the cofactor PY. 39 In addition, the recorded FTIR spectra of β-CD-GSH-CuNCs in the presence and absence of PLP are almost similar (Figure S6), which supported the inclusion of PLP in the hydrophobic inner cavity of β-CD capped over β-CD-GSH-CuNCs. Therefore, as there is no spectral overlap between the fluorescence spectrum of β-CD-GSH-CuNCs and the absorption spectrum of PLP, the photoinduced electron transfer from PLP to the excited NCs along with the copresence of three ligands (GSH, β-CD, and PLP) over the NCs is expected to perturb the fluorescence profile of β-CD-GSH-CuNCs.…”
Section: Resultsmentioning
confidence: 99%
“…The cavity of the functionalized β-CD is suitable to encapsulate the VB 6 cofactor PLP and formed the inclusion complex β-CD/PLP through multiple hydrogen bondings . The recent study revealed that cofactor PLP showed the higher inclusion complexing ability with β-CD than the cofactor PY . In addition, the recorded FTIR spectra of β-CD-GSH-CuNCs in the presence and absence of PLP are almost similar (Figure S6), which supported the inclusion of PLP in the hydrophobic inner cavity of β-CD capped over β-CD-GSH-CuNCs.…”
Section: Resultsmentioning
confidence: 99%
“…The GC5A and FI reporter pair was also chosen to detect turn-on fluorescence in enzymatic substrate Pyridoxal-5′-phosphate ( PLP ) through F-IDA. ( Yue et al, 2019 ).…”
Section: Calix[ N ]Arenes-based Fluorescent Indica...mentioning
confidence: 99%